HIPPONAX' POETIC INITIATION AND HERODAS' 'DREAM'. (30th July 2015) - Cazzato, Vanessa
Abstract : This article presents some fresh evidence in favour of recognising in a series of late testimonia on Hipponax the vestiges of a poem in which the iambist recounted his poetic initiation. It argues that Herodas alludes to such a poem in the opening of his programmatic Mimiamb 1 and in his own account of poetic investiture in Mimiamb 8. Finally, the article attempts an interpretation of this proposed new fragment of Hipponax with the aim of teasing out some of its implications for his poetics.